Adubação orgânica e parcelamento de nitrogênio, fósforo e potássio no abacaxizeiro ‘pérola’ em condições semiáridas - Irineu, Toni Halan da Silva (2019)
Pineapple growing represents a major fruit segment, being the third most tropical fruit produced in the world, being the Northeast responsible for much of the Brazilian production, however, more than 58.11% of this region prevails the semi-arid climate, presenting some limitations as low fertility natural soils, in turn, pineapple is relatively demanding to nutritional aspects, making the practice of fertilization mandatory for commercial purposes. Therefore, the objective was to evaluate organic fertilization and nitrogen, phosphorus and potassium in the 'Pérola' pineapple in semi-arid conditions. The experiments were conducted in the Didactic Orchard, belonging to UFERSA, Campus Mossoró-RN. In experiment I, the experimental design was in randomized blocks, with five treatments and four replications, totalizing 20 experimental plots. We studied mineral fertilization based on NPK and three organic sources (cattle manure, goat manure and chicken litter) and the control. Chemical fertilization was applied 320 kg ha-1 of N and 480 kg ha-1 of K, divided in six times in coverage and 80 kg ha-1 of phosphorus in the furrow. The organic sources were placed the amounts of 10 kg per linear meter in the groove, then the seedlings were planted. In experiment II, the experimental design was DBC, with six treatments and four replications, totaling 24 experimental plots. The treatments were derived from treatment T1 (fertilization recommendation for pineapple), being applied in the groove and in cover, 320, 480, 80 kg ha- 1 of nitrogen, phosphorus and potassium, divided in six times (0, 30, 90, 150, 210 and 270 days after planting). At 18 months after planting, the following parameters were evaluated: plant growth, physical-chemical quality of fruits and crop productivity. The organic fertilization with chicken litter promotes better plant growth results in the physical and chemical characteristics of the fruits, as well as in the productivity of 'Pérola'. The fractionation NPK T5 (where 50% of the phosphorus in the plantation is parceled out and the other 50% in the 150 days after planting) yielded better results of organoleptic quality and yield of 'Pérola' pineapple fruits in semi-arid conditions